Intraoral Prosthetic Chin Augmentation With Vertical Incisions. Issue 3 (May 2018) - Yin, Jiapeng; Fan, Shuqiang; Wu, Xuhong; Pan, Shi; Liao, Lixin; Jin, Guojun
Abstract : Abstract: To explore a new surgical approach for chin augmentation using a prosthesis with 3 intraoral vertical incisions whereby placement of the prosthesis is more convenient and accurate, with fewer postoperative complications. Following the anatomic characteristics of the chin, a bilateral mucosal vertical incision and a median observation incision are made. The V-shaped mark on the upper side of the prosthesis can be seen through the observation incision after it is placed from the lateral incision into the predesigned compartment. The incision can be sutured if there is no bleeding in the operation area. Surgery performed in all 19 patients with mild microgenia with 6 to 12 months of follow-up resulted in satisfactory chin and face shape without any complications. The application of this novel method can correct McCarthy type I microgenia with more accurate positioning, less possibility of bilateral sideways and/or up/down movement, and fewer complications.